NEW ASPECTS OF DIAGNOSTIC AND TREATMENT OF FACIAL NERVE NEUROPATHY IN CHILDREN - Пітик, М. І.; Ліскевич, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
We observed clinical course of facial nerve neuropathy in 48 children who were treated with Thiotriazoline and Neiromidin. Assessment of clinical signs of autonomic dysfunction, heart rate variability and dynamics of electroneuromyographic changes were performed. Increasing of autonomic reactivity and optimizing of electromyographic signs of neuromuscular dysfunction were more pronounced in children who were treated with Thiotriasolin and Neiromidin.